Carbon Supported Nanocrystalline Manganese Oxide: Surpassing Platinum as Oxygen Reduction Catalyst in Direct Borohydride Fuel Cells. Issue 8 (1st January 2016) - Grimmer, Christoph; Grandi, Maximilian; Zacharias, Robert; Weinberger, Stephan; Schenk, Alexander; Aksamija, Enes; Mautner, Franz-Andreas; Bitschnau, Brigitte; Hacker, Viktor
Abstract : Manganese oxide (MnO2 ) nanodispersed on high surface area carbon was tested as cathode catalyst for direct borohydride fuel cells with an anion conducting membrane. In order to investigate the effects of borohydride crossover, ex-situ experiments toward oxygen reduction reaction were conducted employing rotating disk electrodes in presence of borohydride and thiourea. Although platinum showed superior catalytic properties at ideal conditions, manganese oxide outperformed platinum significantly in presence of borohydride. Direct borohydride fuel cell tests were conducted using Pt/C-based and MnO2 /C-based. After one hour of operation at 0.40 V the platinum based membrane electrode assembly lost approx. 30% of its initial peak power density while the non-precious metal MEA showed constant performance. The peak power density of the single test cell with a Pt/C based anode, an anion exchange membrane and a MnO2 /C based cathode was 38 mW cm −2 .